Locating the British Library Additional 14912 calendar. (1st December 2019) - Luft, Diana
This article advances the argument that the fourteenth-century Welsh medical manuscript British Library Additional 14912 is based on materials which ultimately stem from Llanthony Prima Priory in Monmouthshire, although it may itself have been produced for a patron in the vicinity of Caerleon. The argument is based primarily on the saints' feasts which appear in a calendar which precedes the medical material in the manuscript. The feast which stands out is that of St. Finnian of Clonard, which is noted on December 12, and which is also used to calculate that month's Ember Days. The article traces the close relationship between Llanthony and Finnian's native Westmeath, and argues that Llanthony's status as an Augustinian priory may account for that foundation's apparent interest in Welsh medical material. This interest may also be seen in the closely-related fourteenth-century Welsh medical manuscript Cardiff 3.242, which may also be a product of Llanthony.